Mixed Homotopy Integral Transform Method for Solving Non-Linear Integro-Differential Equation - F. Kadhem, Mohanad; H. Alfayadh, Ali (Al-Nahrain Journal of Science, 2022)
In this paper, we have applied Sawi transform with homotopy perturbation method to obtain analytic approximation for non-linear integro-differential Equations. The proposed technique is compared with homotopy perturbation method and Abood transform homotopy perturbation method. The results show that Sawi transform homotopy perturbation is an efficient approach to solve non-linear integro-differential equations.